ARAHAN PENATAAN KAWASAN BERBASIS MITIGASI BENCANA BANJIR DI SEMPADAN SUNGAI TAMIANG KECAMATAN SERUWAY - Maghfira Khusnul Alia; Ferad Puturuhu; Rifyan Ruman (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT This research aims to determine the direction for area planning based on flood disaster mitigation along the banks of the Tamiang River in Seruway District, Aceh Tamiang Regency, Aceh Province. Specifically in the villages of Pekan Seruway and Muka Sungai Kuruk, which are the two villages most affected during floods caused by the overflow of the Tamiang River, resulting in the breaching of levees. The riverbank area in these two villages has a high level of flood vulnerability, thus requiring guidelines for area planning based on flood disaster mitigation. This study employs an Overlay method by combining 5 flood vulnerability parameters: slope steepness, elevation, land use, rainfall, soil type, and river buffer, to obtain the level of flood vulnerability, and then uses Triangulation analysis to determine the area planning direction. The research results show that the flood vulnerability level is divided into 3 classifications: high, medium, and low. The border area of the Tamiang River is at a high risk level, thus requiring guidance for area arrangement using Triangulation analysis, resulting in an area arrangement directive based on flood disaster mitigation, which includes rehabilitation and the construction of permanent embankments with public open space at the riverbank as a buffer zone. This research is expected to serve as a reference in determining directives for area arrangement based on flood disaster mitigation at the riverbank. ABSTRAK Penelitian ini bertujuan untuk menentukan arahan penataan kawasan berbasis mitigasi bencana banjir pada sempadan Sungai Tamiang di Kecamatan Seruway, Kabupaten Aceh Tamiang, Peovinsi Aceh. Khususnya di Desa Pekan Seruway dan Desa Muka Sungai Kuruk yang merupakan dua desa paling terdampak saat terjadi banjir akibat luapan air Sungai Tamiang sehingga menyebabkan jebolnya tanggul. Kawasan sempadan Sungai tamiang di kedua desa tersebut memiliki tingkat kerawanan banjir yang tinggi sehingga diperlukan arahan penataan kawasan berbasis mitigasi bencana banjir. Penelitian ini menggunakan metode Overlay dengan menggabungkan 5 parameter kerawanan banjir yaitu kemiringan lereng, ketinggian, penggunaan lahan, curah hujan, jenis tanah, dan buffer sungai untuk memperoleh tingkat kerawanan banjir dan kemudian menggunakan analisis Triangulasi untuk menentukan arahan penataan kawasan. Hasil penelitian menunjukkan bahwa tingkat kerawanan banjir terbagi menjadi 3 klasifikasi yaitu tinggi, sedang, dan rendah. Kawasan sempadan Sungai Tamiang berada di tingkat kerawanan tinggi sehingga dibutuhkannya arahan penataan kawasan yang menggunakan analisis Triangulasi sehingga menghasilkan arahan penataan kawasan berbasis mitigasi bencana banjir yang berupa rehabilitasi dan pembuatan tanggul permanan dengan ruang terbuka publik di sempadan sungai sebagai zona penyangga. Penelitian ini diharapkan dapat menjadi acuan dalam menentukan arahan penataan kawasan yang berbasis mitigasi bencana banjir pada sempadan sungai.